INTRODUCTION AND IMPORTANCE OF ROBOTICS - Sharma, Indrani; Chauhan, Pawan Singh; Jakhar, Shyo Prakash; Mishra, Adarsh (International Journal of Psychosocial Rehabilitation, 2020)
What is a robot? "a reprogrammable, multi-functional manipulator designed to move material, parts, tools, or specialized devices through variable programmed motions for the performance of a variety of tasks" is the definition of an industrial robot given by the robot industries association (ria). The scientific field of robotics focuses on the creation, application, and maintenance of mechanical robots in technology and engineering. The field of robotics is the fusion of science, engineering, and design that produces robots—machines that mimic or replace human behaviour. Pop culture has long piqued the interest of robotics in r2-d2 from the prime optimus. E-wall. Humanoid robot designs generally sound like parodies of the genuine thing. Perhaps they are still more progressive than we realize. With time robots have been gaining structural and intellectual capacities, which does not rule out the potential of an r2-d2 like gadget in the future. In the automotive industry, 90% of all robots were used in the production of cars in 2005. The main element of these robots is mechanical arms used to screw or solder other car parts. As of right now, the field of robotics has expanded and grown to include the development, production, and implementation of robots that can operate in the most difficult environments on earth, assist law enforcement, and even assist in nearly every aspect of healthcare. Even though the automotive industry is still in its infancy, amazing progress has already been made. From the deepest depths of space to the lowest seas, robots are seen accomplishing feats that humans could never imagine. The idea of robotics in the modern world will be addressed in this paper. In the fields of manufacturing and science, robotics is one of the most well-known divisions. Here, engineers work consistently to create robots that can perform specific tasks and produce the right results. As technology advances, every engineer hopes to have a robot with zero errors, but this is becoming increasingly impossible to attain. We can consider it, but 0% still doesn’t mean that there won’t be any errors—rather, it means that you will always receive the right response to every question.